Tata Ruang Penempatan Stasiun Srono di Banyuwangi - Baskara, I Made Putra; Agung Bawono, Rochtri; Puji Astiti Laksmi, Ni Ketut (Humanis; Vol 29 No 1 (2025), 2025)
Staatsspoorwegen once built a railway line in Banyuwangi connecting Rogojampi and Benculuk. The railroad line has supporting facilities in the form of stations. One of the stations owned by the Rogojampi-Benculuk line, namely Srono Station. The purpose of this study is to determine the spatial condition of the placement of Srono Station.  This research is a qualitative research with a spatial approach. The data used in this research are primary and secondary data. Primary data used are observation and interview data obtained in the field, while secondary data used are literature studies (journals, books, colonial published magazines, and colonial published newspapers) and colonial published maps. Both data were analyzed using a spatial approach and presented in descriptive form. The analysis that has been done shows that the construction of the station adjacent to the T-junction of Kebaman Village, Srono Subdistrict was not built without reason, but was well considered. The spatial placement of Srono Station, which is adjacent to the road junction, provides benefits in terms of accessibility, economy, and environmental changes.